An investigation of mosaic/chimaerism in the domestic horse (Equus caballus caballus) : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Cytogenetics at Massey University - Walker, Karen Sheila (Massey University, 1980)
This study involved three aspects of the field of Cytogenetics applied to the domestic horse (E. caballus caballus). The first aspect, the identification and investigation of individuals with cytogenetic anomalies, is fundamental to Cytogenetics. The individuals discovered, however, pointed to the close interrelationship of Cytogenetic and Genetic research. Thirdly, questions of fertility, and in one mare the tentative demonstration of an application of cytogenetics in veterinary clinical evaluation, were concerned with functions of Clinical Cytogenetics. The primary hypothesis of this study was that individuals with abnormal sex chromosome constitutions, the majority of which are either mosaics or chimaeras, form a significant proportion of some E. c. caballus breeds, in particular the Thoroughbred Breed. Subsidiary to that hypothesis was that these mosaic/chimaeras as a group were disproportionately responsible for the sub-fertility of some horse populations, through infertility, sub-fertility and generating abnormal offspring. Five horses were investigated. One, a XY/XYY/?XO mosaic/chimaeric stallion was fully fertile. However, he sired an XO still-born filly. Limited studies of three of his relatives and three of his other progeny, suggested the possibility of cytogenetic anomalies in that kinship. He was the first reported stallion with an XYY line, and his XO filly was the first reported still-born foal with a chromosome abnormality. Two 64,XX/65,XXY mares with no physical signs of intersexuality were studied. One was infertile, however, there was insufficient information to assess the other mare's fertility. An infertile mare was discovered and investigated in depth, which had 65,XXX/65,XXY/ 64,XX/66,XXY/66,XXXX mixoploid mosaic/chimaerism, although she was primarily a triple-X mare. The fourth mare was primarily thought to be a proliferative mosaic, which exhibited mitotic instability. Post mortem evidence, however, confirmed that she had been cytogenetically abnormal and that she probably was a mosaic/chimaera. Aside from one XX/XXY mare, which had been born with congenital defects, there was nothing either in the history or phenotype of these five horses to distinguish them from other Thoroughbreds. Only one of the mares was presented for analysis because of infertility, although two of the other mares might have been termed "shy breeders". The discovery of all the major sex chromosome aneuploid conditions infrequently found in humans, XO, XXY, XYY and XXX, in the mosaic/chimaeric condition among less than 200 Thoroughbreds evaluated, suggested that chromosome anomalies are prevalent in the Thoroughbred population.
Keywords: Cytogenetics; Horse genetics; Chromosome analysis; Horse breeding